2019
DOI: 10.1001/jamadermatol.2019.0066
|View full text |Cite
|
Sign up to set email alerts
|

Variance of Basal Cell Carcinoma Subtype Reporting by Practice Setting

Abstract: Ms Morrison had full access to all the data in the study and takes responsibility for the integrity of the data and the accuracy of the data analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…The correct assessment of the subtype is crucial for planning the relevant treatment. However, there is a significant inter-pathologist variability when grading tumors 8 and reporting the subtype 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%
“…The correct assessment of the subtype is crucial for planning the relevant treatment. However, there is a significant inter-pathologist variability when grading tumors 8 and reporting the subtype 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Tumor location divided by Mohs appropriate use criteria regions. 8 “H” refers to mask areas of central face, “M” refers to cheeks, forehead, scalp, neck, and jawline, and “L” refers to trunk and extremities. Area H (orange) had 106 aggressive subtypes found on Mohs of the 291 nonaggressive biopsies from the region.…”
Section: Resultsmentioning
confidence: 99%
“…Of note, our group has previously observed that 10% of referred patients had no specification of BCC subtype, almost half of whom had aggressive histology on Mohs. 8 Although BCCs lacking subtypes on biopsy reports were excluded from our analyses, it is worth noting that in practice, differences in reporting patterns may contribute to an even higher misrepresentation on biopsy of a tumor's true aggressiveness.…”
Section: Discussionmentioning
confidence: 99%
“…After an initial qualitative review by the steering group, consultation of the current literature and exclusion of subtypes not suggested by at least four experts, the included subtypes comprised nodular BCC, superficial BCC and less common variants (encompassing infiltrative and morpheaform BCCs). [27][28][29] The number of proposed image features for each specific BCC subtype varied from 0 to 40. The terminology for seven image features (25 words in total) was synonyms.…”
Section: First Delphi Roundmentioning
confidence: 99%